Prophylactic mastectomy and occult malignancy: Surgical and imaging considerations. Issue 1 (7th September 2022) - Thompson, Jessica L.; Sinco, Brandy R.; McCaffrey, Rachel L.; Chang, Alfred E.; Sabel, Michael S.; Dossett, Lesly A.; Hughes, Tasha M.; Jeruss, Jacqueline S.
Abstract: Background: Sentinel node biopsy (SLNB) is not routinely recommended for patients undergoing prophylactic mastectomy (PM), yet omission remains a subject of debate among surgeons. A modern patient cohort was examined to determine occult malignancy (OM) incidence within PM specimens to reinforce current recommendations. Methods: All PM performed over a 5‐year period were retrospectively identified, including women with unilateral breast cancer who underwent synchronous or delayed contralateral PM or women with elevated cancer risk who underwent bilateral PM. Results: The study population included 772 patients (598 CPM, 174 BPM) with a total of 39 OM identified: 17 invasive cancers (14 CPM, 3 BPM) and 22 DCIS (19 CPM, 3 BPM). Of the 86 patients for whom SLNB was selectively performed, 1 micrometastasis was identified. In the CPM cohort, risk of OM increased with age, presence of LCIS of either breast, or presence of a non‐ BRCA high‐penetrance gene mutation, while preoperative magnetic resonance imaging was associated with lower likelihood of OM. Conclusions: Given the low incidence of invasive OM in this updated series, routine SLNB is of low value for patients undergoing PM. For patients with indeterminate radiographic findings, discordant preoperative biopsies, LCIS, or non‐ BRCA high‐penetrance gene mutations, selective SLNB implementation could be considered.